PERCEPTION OF BODY IMAGE AMONG PEOPLE ENGAGED IN SPORTS ON A REGULAR BASIS - Szűcs, Róbert Sándor; Pólya, Éva; Szakály, Zoltán (Acta Carolus Robertus, 2020)
Relationship between body and self-image is a well-known and frequently investigated process, however especially among athletes this area has been accentuated till the last decades in the literature. In our paper we investigate the attitude of people engaged in sports on a regular basis primary concentrating on perception of their body image, the type and form of sport activities. People who took part in our research are engaged in sports on a regular basis, they do sport activities at least once a week on their own free will. Paper assisted personal and online interviews were used, we were primary concentrating on the attitudes of the respondents. Size of the sample is 737 persons. During our research we came to the conclusion that subjectively perceived „normal” body shape category moving higher and the social judgement of overweight became more and more accepted. Owing to the ideal body shape presented by the consumer society slimmer people want to become thicker, people with a stronger shape want to become leaner. Hence a social problem come into being that only exist in the athlete’s mind. This phenomenon can fundamentally base the headway of food supplements since the producers offer solutions to all segments’ real or putative problems
Keywords: Body image; People engaged in sports on a regular basis; Food supplements; Attitude